PENGARUH TOKOH SUPERVILLAIN DALAM FILM SUPERHERO - Mekka Syed Nury (Institut Seni Budaya Indonesia Bandung, 2022)
ABSTRACT Superhero movie is a film that tells the story of a superhero fight against crime. In the story of his struggle, the superhero character often passes many obstacles for his purpose to stop the ambition of the villain in creating chaos in the world. Analysis of supervillain characters in this paper based on the theory of causality, where in the description, the author tries to compare the results that occur if the character supervillain successfully carry out his ambition with the result that occurs if the supervillain character fails to carry out his ambition, The results of the study can also illustrate how the influence of the supervillain character in the superhero film. There are many criminals that we know from superhero movies. Many also memorable figures such as The Joker, or Loki. Among the many superhero characters, there are some figures who have an interesting ambition, where the ambition will make us curious if the ambition of the villain is achieved. Will that ambition bring life in this world for the better, or even worse. ABSTRAK Film superhero adalah film yang mengisahkan perjuangan seorang pahlawan super melawan kejahatan. Dalam kisah perjuangannya, sang tokoh superhero kerap melewati banyak rintangan demi tujuannya untuk menghentikan ambisi sang penjahat dalam menciptakan kekacauan di dunia. Analisis karakter supervillain yang ada di dalam tulisan ini berdasarkan teori kausalitas, dimana di dalam paparannya, penulis mencoba membandingkan akibat yang terjadi jika sang tokoh supervillain berhasil melaksanakan ambisinya dengan akibat yang terjadi jika sang tokoh supervillain gagal melaksanakan ambisinya. Hasil dari teori tersebut juga dapat menggambarkan bagaimana pengaruh sang tokoh supervillain di dalam film superhero. Ada banyak tokoh penjahat yang kita kenal dari film-film superhero. Banyak juga tokoh memorable seperti The Joker, atau Loki. Di antara banyaknya tokoh superhero, ada beberapa tokoh yang memiliki ambisi yang menarik, dimana ambisi tersebut akan membuat penasaran jika seandainya ambisi sang penjahat tersebut tercapai. Akankah ambisi itu membawa kehidupan di dunia ini menjadi lebih baik, atau sebaliknya.